Morland, Graham County - Helberg, Scott (Kansas State University, The Chapman Center for Rural Studies, 2010)
Morland was first known as Fremont, it was named after General John C. Fremont who was the noted explorer. The people of Morland fought hard for their survival and in the end it paid off. Just the thought that a railroad could be coming gave people that little faith they needed to continue. New businesses started and old businesses lasted. The railroad was the life support they needed to last 129 years. The railroad was discontinued in 1998 and businesses slowly began to die off, but the town has not fallen off the map.
Scott Helberg, “Morland, Graham County,” Chapman Center Research Collections, accessed October 26, 2020, https://ccrsresearchcollections.omeka.net/items/show/23.
Keywords: Fremont; Fremont Weekly Star; Graham County; Morland; Plainville Branch; Solomon River